Winesburg, Ohio - Anderson, Sherwood, 1876-1941. (New York : Bantam Books, 1995)
A collection of interrelated stories in which George Willard, a young newspaper reporter, comments on the hopes, dreams, and fears of the residents of the small town of Winesburg, Ohio.
Adult
Keywords: City and town life -- Ohio -- Fiction; City and town life -- Ohio -- Fiction; Ohio -- Social life and customs -- Fiction; Ohio -- Social life and customs -- Fiction